Model Korelasi Volume, Kecepatan Dan Kepadatan Lalu Lintas (Studi Kasus Jalan RTA. Milono Kota Palangka Raya) : Traffic Volume, Speed And Density Correlation Model (Case Study Of Milono RTA Road, Palangka Raya City) - Puspasari, Nirwana; Akbar, Reza Zulfikar; Utama, M. Gemilang Pria (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Traffic conditions on road sections always vary and are never the same. This variation can be seen not only in the amount of traffic volume, but also in the variation of traffic speed and density on the road section. The more traffic volume that passes through a road section, the less the speed of the vehicle and the denser the road section. To find out the relationship between these variables, the author tries to analyze the correlation model of traffic volume, speed and density. This research was conducted on the RTA. Milono road for 2 days, namely Monday and Tuesday. Traffic volume data and average vehicle travel time were taken during the morning, afternoon and evening peak hours for 2 hours each, namely 06.00-08.00 am, 11.00-13.00 pm and 16.00-18.00 pm. The number of samples of vehicle travel time was taken as many as 98 pieces for each direction A and B based on the Slovin formula. Data analysis using Greenshield method, or linear regression, which is a model consisting of 2 variables x and y, where traffic speed as variable y and road density as variable x, test the correlation between the two variables using R2. The correlation model of vehicle speed with density from the data analysis results obtained 6 models, with the highest R2 given by the model Y = 58,72 – 0,67 X with R2 = 0,94 indicating that 94% of the traffic density data is linearly connected with vehicle speed. The model of the relationship between traffic volume and density is Q = 58.72D - 0.67D2 and the model of the relationship between traffic volume and speed is Q = 87.67Vs - 1.493Vs2. The three models show that as the traffic density increases by 1 vehicle/km on road section B will have an impact on decreasing the speed by 0,67 km/h, and as the density increases by D vehicles/km on road section B will have an impact on reducing the traffic volume by 0.67D2 SMP/h and shows as the speed increases by Vs (km/h) on road section B will have an impact on reducing the traffic volume by 1.493Vs2 (SMP/h). Then the increase in traffic volume on the road, will cause a decrease in speed and an increase in the density of vehicles on the road, which causes the level of service of the road to also be lower.